The numerical solution of non-Newtonian Reiner--Philippoff hybrid nanofluid over a shrinking wedge with magnetohydrodynamic effects - Nur Syahidah, Nordin; Abdul Rahman, Mohd Kasim; Masyfu'ah, Mokhtar; Khairum, Hamzah; Iskandar, Waini (Institute of Physics, University of Latvia, 2024)
The study examines the behavior of a non-Newtonian Reiner-Philippoff hybrid nanofluid as it flows towards a permeable shrinking wedge. It accurately investigates shear thickening (dilatant) and shear thinning (pseudo-plastic) behaviors in specific fluids. The widely used heat transfer fluid GO-MoS2 with a water base was used in the study. The model is based on theoretical assumptions to form governing equations, which are then simplified to ordinary differential equations. These equations are solved using the MATLAB software bvp4c. The results of this study presented visually and in a table form, reveal that hybrid nanofluids have a far more substantial impact on fluid characteristics and produce more satisfactory results than regular nanofluids. The presence of magnetohydrodynamic (MHD) effect in a hybrid nanofluid substantially impacts the fluid characteristics and produces better outcomes. It has been also found in the study also that the temperature profiles are greatly improved by increasing the volume fraction of hybrid nanofluids. In conclusion, these findings strongly suggest that hybrid nanofluids could be a promising solution for improving fluid dynamics and heat transfer in different applications, paving the way for further research and development in this area and sparking interest in the potential for future studies.